Pembentukan dan Perkembangan Parmusi Cabang Padang Pariaman (1968-1971) - Irmun Irmun (Analisis Sejarah, 2024)
This study examines the formation and development of the Indonesian Muslim Party (Parmusi) Branch in Padang Pariaman during the period 1968-1971. Parmusi was established in 1968 with the goal of reviving the legacy of Masyumi, which was disbanded by Soekarno. The establishment of the Parmusi branch in Padang Pariaman was formalized through Decree Number 214/1/1968. Although initially expected to become a new political force, Parmusi faced various challenges, including intervention from the New Order government and Laksusda. Under the leadership of Raisuddin Muchtar and Alhadar Alam, Parmusi endeavored to consolidate support and participate in the 1971 elections, despite encountering electoral fraud and political pressure. Parmusi’s campaign and political activities were often closely monitored by intelligence and government officials. The results of the 1971 elections showed that Parmusi secured 7 seats in the Padang Pariaman Regional House of Representatives, although it remained under the dominance of Golkar. This study provides insights into local political dynamics and the struggles of an Islamic political party amid state surveillance and intervention.